Closed-form solutions of a fishery harvesting model with state constraint - Puchkova, A.; Rehbock, Volker; Teo, Kok Lay (John Wiley and Sons, Ltd., 2013)
We derive a closed-form solution for a well-known fisheries harvesting model with an additional state constraint. The problem is linear in the control and previous solutions appearing in the literature have been numerical in nature. The so-called direct adjoining approach is used in our derivation and the optimal solutions turn out to be a mixture of bang-bang and boundary arcs.